The Relationship Between Religiosity and Self-Compassion in Breast Cancer Patients Post Mastectomy Surgery - Nisa Nabila Sandy; Mulia Hakam; Murtaqib Murtaqib (NurseLine Journal, 2023)
In Indonesia, the prevalence of breast cancer is quite high, from report data (Riskesdas, 2018) stating that breast cancer reaches 42.1% with an average death rate of around 17%. The type of treatment that is often used by breast cancer patients is a mastectomy. Masectomy raises physical and psychological impact. The current phenomenon is that many women experience some level of psychosocial pressure during their cancer journey, which can have an impact on issues of faith or religiosity, self-compassion, and quality of life (Hewit et al, 2019). The research design conducted by researchers is observational analytic with a cross sectional approach. The population in this study were breast cancer patients after mastectomy surgery at Dr. Soebandi Jember and the sample of this study were 38 respondents. The religiosity analysis in this study found that the religiosity study of patients who experienced breast cancer post-masectomy surgery obtained that the median value of the religiosity variable was 60.00 with the lowest value being 23 and the highest being 64. Meanwhile, the self-compassion analysis found that self-compassion research on patients who experienced breast cancer after mastectomy surgery found that the median value of the self-compassion variable was 94.50 with the lowest value being 65 and the highest being 98. Analysis using Pearson Product moment obtained a p-value of 0.000 less than 0.05 so that the Ha hypothesis is accepted or it can be said that there is a relationship between religiosity and self-compassion in post-massectomy breast cancer patients at Dr. Soebandi Jember.